Dynamics of cavitation zone development during sonication of suspensions of magnesium particles - Brezhneva, Nadzeya Yu.; Minchuk, Vyacheslav S.; Ulasevich, Sviatlana A.; Dezhkunov, Nikolai V.; Skorb, Ekaterina V. (Journal of the Belarusian State University. Chemistry, 2021)
The cavitation activity during ultrasonic treatment of magnesium particles has been investigated. The cavitation activity recorded in a continuous mode of ultrasonic treatment altered in a wide range at constant output parameters of the generator. The rate and nature of cavitation activity variation depended on the mass fraction of particles in the suspension. It has been demonstrated that during the ultrasonic treatment of magnesium aqueous suspensions it is possible to determine the following stages: growth of cavitation activity, reaching a maximum followed by a decrease and reaching a plateau (or repeated cycles of increasing or decreasing cavitation activity). The complex nature of the cavitation activity dynamics is associated with the participation of hydrogen released as a result of the chemical interaction of magnesium particles with water in the formation of the cavitation zone. The magnesium particles modified with ultrasound were characterised with the use of scanning electron microscopy, X-ray phase analysis and thermal analysis. It has been found that ultrasonic treatment of magnesium particles resulted in the formation of magnesium hydroxide and magnesium hydride phases.
Keywords: ultrasound; cavitation activity; magnesium microparticles; Mg(OH)2; MgH2